Serramento do aço ABNT 1045 utilizando serras circulares com insertos de metal duro e cermet - Maria Cristina Moreira (2011)
The principal aim of this work is to evaluate the influence of machining parameters on the performance of circular sawing of AISI 1045 steel using saw blades with tungsten carbide and cermet inserts. More specifically, the influence of cutting speed, feed rate and both insert geometry and material on feed, radial and axial forces, machined surface roughness (Ra, Rq, Rt and Rz), width of cut, burr formation, tool wear and chip forms will be investigated. Firstly, the influence of cutting speed and feed rate in addition to their interaction on the output parameters (forces, surface roughness and gap width) will be assessed using analysis of variance. Next, the performance of the three circular saw blades will be carried out with the aid of box plot graphs (sample dispersion) and both mean values and standard deviations. Finally the surface response method will be employed to optimize the cutting parameters for each saw blade in order to identify the cutting speed and feed rate responsible for lowest forces and best surface finish. In general, the results indicated that the carbide saw with pre-cutter and cutter geometry was responsible for lowest sawing forces, which decreased as cutting speed was elevated and increased together with feed rate. With regard to the machined surface roughness and width of cut, best results were obtained using the cermet saw blade. The optimization results showed that the carbide saw blade with alternating slots promoted lowest forces and best surface finish together with highest metal removal rate. Burr formation and chip forms were affected by the insert geometry/material, albeit the influence of the cutting parameters was found to be negligible. Finally, gradual wear was observed on the cermet saw blade, whereas the tungsten carbide inserts presented appreciable chipping.